Makna Teologis 1 Timotius 2:11–12 dan Implikasinya dalam Peran Perempuan serta Pertumbuhan Spiritualitas Jemaat - Aruan, Josephin Andriano; Pardosi, Milton (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to examine and analyze the theological meaning of the phrase "women remain silent" in 1 Timothy 2:11, 12 and its implications for the role and involvement of women and its impact on the spiritual growth of the Seventh-day Adventist Church (GMAHK) congregation in the Pangkalan Kerinci area. This article shows that the commandment to "keep silent" is not an absolute commandment and prohibition against women's ministry but rather a situational one in which it has the basis of the rampant heretical teaching practiced by women in Ephesus at that time. The command was an effort to prevent false teaching in Ephesus. It is evident that women's involvement in ministry has a positive impact on the dynamics of worship and the spiritual growth of the congregation. Therefore, the church must understand the context of this text and open up equal spaces of ministry based on the gift of the Holy Spirit and not gender restrictions.